Model Pembelajaran E-Learning dan Pelatihan Softskill Tenaga Keperawatan terhadap Mutu Pelayanan Keperawatan - Kusumawardani, Nila; Indasah, Indasah; Prasetyo, Joko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of e-learning learning models and soft skill training for nursing staff on the quality of nursing services at Restu Kasih Hospital. The method is genuinely experimental and uses a pre-post-test control group design. The study results showed that before e-learning was carried out in the intervention group, almost all of the quality was in the sufficient category of 52 people (89.7%). Before soft skill training was carried out in the control group, almost all of the quality was in the sufficient category of 48 people (84.2%). After e-learning was carried out in the intervention group, nearly all of the quality was in the excellent category of 51 people (87.9%). After soft skill training was carried out in the control group, almost all of the quality was in the sufficient category of 48 people (84.2%). In conclusion, there is a significant influence between the e-learning learning model and soft skill training for nursing staff on the quality of nursing services at Restu Kasih Hospital. Keywords: Nursing Service Quality, E-Learning, Soft Skill Training